#### Answer

$x=1$

#### Work Step by Step

Using properties of equality, the solution to the given expression, $
-3(x-4)+x=5(3-x)
$, is
\begin{array}{l}
-3x+12+x=15-5x
\\\\
-2x+5x=15-12
\\\\
3x=3
\\\\
x=\dfrac{3}{3}
\\\\
x=1
.\end{array}

Published by
Pearson

ISBN 10:
0321785045

ISBN 13:
978-0-32178-504-6

$x=1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.